Exploration of charge transport materials to improve the radiation tolerance of lead halide perovskite solar cells. Issue 12 (18th May 2022) - Murakami, Yoshiyuki; Nishikubo, Ryosuke; Ishiwari, Fumitaka; Okamoto, Kazumasa; Kozawa, Takahiro; Saeki, Akinori
Abstract : Towards the application of perovskite solar cells (PSCs) in space, we extensively investigated the effects of electron beam irradiation on binary-mixed PSCs with various hole- and electron-transport materials. Abstract : Organic–inorganic lead halide perovskite solar cells (PSCs) are well suited for use in spacecrafts owing to their potentially high radiation tolerance and high mass specific power. However, the optimal device structure and charge transport material (hole-transport material, HTM; electron transfer material, ETM) have remained elusive. Herein, we extensively investigated the effects of electron beam (EB) irradiation (100 keV up to 2.5 × 10 15 cm −2 ) on binary-mixed PSCs (MA0.13 FA0.87 PbI2.61 Br0.39, MA: methylammonium cation, FA: formamidinium cation) of regular (ETM on a transparent conductive oxide, TCO) and inverted (HTM on a TCO) structure types comprising different HTMs (Spiro-OMeTAD, CuSCN, PEDOT:PSS, 2PACz, PTB7, and PTAA) and ETMs (TiO2, C60, and PCBM). In addition to comparing these organic/inorganic HTMs/ETMs and device structures of the regular and inverted types, we separately evaluated the EB irradiation effect on each layer using time-resolved microwave conductivity measurements and various spectroscopic techniques. Based on the characteristics and degradation mechanism revealed, a regular structure using PTAA as the HTM was found to have the highest radiation tolerance. Our results provide a comprehensive understanding of radiation damage and pave the way for the application of PSCs in space.